Proceedings of the 21st International Conference on World Wide Web 2012
DOI: 10.1145/2187980.2188168
|View full text |Cite
|
Sign up to set email alerts
|

Investigating bias in traditional media through social media

Abstract: It is often the case that traditional media provide coverage of a news event on the basis of journalists' viewpoints -a problem termed in the literature as media bias. On the other hand social media have given birth to an alternative paradigm of journalism known as "citizen journalism". We take advantage of citizen journalism to detect the bias in traditional media and propose a simple model for empirical measurement of media bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Despite having high popularity among its viewership, mainstream media often fails to meet the standards of journalism ethics, and inadvertently patronises certain ideas [5]. Furthermore, news sources are also known to inject political bias while reporting [9], [17], [18], potentially affecting the political beliefs of the audience, which might result in altering voting behaviour [18]. Recently it was shown that Fox News had been misrepresenting facts in an effort to appeal to conservative viewers [6].…”
Section: Related Workmentioning
confidence: 99%
“…Despite having high popularity among its viewership, mainstream media often fails to meet the standards of journalism ethics, and inadvertently patronises certain ideas [5]. Furthermore, news sources are also known to inject political bias while reporting [9], [17], [18], potentially affecting the political beliefs of the audience, which might result in altering voting behaviour [18]. Recently it was shown that Fox News had been misrepresenting facts in an effort to appeal to conservative viewers [6].…”
Section: Related Workmentioning
confidence: 99%
“…Diehl et al, (2013) suggested bias between social media and online data and explored how interaction between journalists and people on Twitter affects perceptions of bias. Younus et al (2012) researched how social media can identify bias in traditional media, introducing the concept of citizen journalism and creating a model using latent Dirichlet allocation and Jaccard similarity to measure bias. Thomsen (2018) used sentiment analysis to study media bias in newspaper tweets and discovered that while some media companies showed bias, most did not.…”
Section: Biasmentioning
confidence: 99%
“…Morgan et al [43] found that Twitter users share news in similar ways regardless of outlet or perceived outlet ideology, and that as users share more news content, they tend to quickly include outlets with opposing views. Younes et al [62] looked at how traditional media outlets and social media differ in coverage of an event, and focused on coverage patterns of NYTimes articles and tweets during the Egyptian uprising in 2011. To discover such patterns, they proposed a simple media bias measurement model for day-to-day news items built on top of topic models.…”
Section: Twitter For Crisis and Controversy Understandingmentioning
confidence: 99%